360º Narrative videos.: An Analysis model proposa (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
Given the need to define the audiovisual language of virtual reality films and the lack of research in this area, we propose a model of analysis focused on 360º narrative videos. The model was made up of variables and categories that could be used to guide the viewer´s gaze through the spherical image. The validity of the model was confirmed through a pretest.
Keywords: Virtual Reality; Audiovisual Language; 360º Videos; Cinematic VR; Narrative